Answer:
The correct answer is C, x = 1; x = -8
Step-by-step explanation:
- Quadratic formula: [tex]x=\frac{-b\±\sqrt{b^2-4ac}}{2a}[/tex]
[tex]x^2+7x=8[/tex]
[tex]x^2+7x-8=0[/tex] <== a = 1, b = 7, c = -8
[tex]x=\frac{-b\±\sqrt{b^2-4ac}}{2a} \\\\x=\frac{-7\±\sqrt{7^2-4*1*-8}}{2*1} \\\\x=\frac{-7\±\sqrt{7^2-4*-8}}{2} \\\\x=\frac{-7\±\sqrt{49+32}}{2} \\\\x=\frac{-7\±\sqrt{81}}{2} \\\\x=\frac{-7\±9}{2} \\\\x=\frac{-7+9}{2}\ \ and\ \ x=\frac{-7-9}{2} \\\\x=\frac{2}{2}\ \ and\ \ x=\frac{-16}{2} \\\\x=1\ \ and\ \ x-8\\\\x=1,\ x-8[/tex]
Hope this helps!